Evaluación de un promotor de rendimiento biológico (Megasom) en el engorde de cerdos en el Barrio Yanayacu del cantón Salcedo - Buenaño Ocaña, Milton Mariano (2011)
This research was conducted in the province of Cotopaxi, Canton Salcedo, Barrio Yanayácu. A total of 16 weaned pigs distributed in the corresponding treatments with a weaning age of 28 days of age. The following 7 treatments to investigate the references are: T1 (0.5 ml.2 dose), T2 (0.5 ml. 1 dose), T3 (1ml. 2 doses), and T4 (1 ml. 1 dose), T5 ( 1.5 ml. 2 doses), T6 (1.5 ml. 1 dose), T7 (control). The ages at which such measurements were made were: Initial, 42, 56, 70, 84, 98, 112, 126, 140, and 154 days old. At 70 days of age the second dose was applied in R1 Megasom treatments 1 to 6. We applied a completely randomized design (DCA) with comments. The parameters evaluated by analysis of variance (ANDEVA), and mean of the variables under study each of the treatments according to Duncan test, considering a significance level of 5%....